Legendre polynomial coefficients in the analysis of the force plate measurements from an osteoarthritic gait - Khodadadeh, S. (Journal of biomedical engineering, 1985)
The assessment of force plate measurements obtained from subjects with a pathological gail is normally carried out by a visual inspection of the force-time curves produced by the plate. It is shown that a valuable addition to that inspection is the derivation from the curves of Legendre polynomial coefficients, the first five coefficients being sufficient to indicate clearly, specific osteoarthritic abnormalities.